2010
DOI: 10.1186/1471-2318-10-70
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia predicts mortality in critically ill elderly patients with sepsis

Abstract: BackgroundAdvanced age is one of the factors that increase mortality in intensive care. Sepsis and multi-organ failure are likely to further increase mortality in elderly patients.We compared the characteristics and outcomes of septic elderly patients (> 65 years) with younger patients (≤ 65 years) and identified factors during the first 24 hours of presentation that could predict mortality in elderly patients.MethodsThis study was conducted in a Level III intensive care unit with a case mix of medical and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 30 publications
(41 reference statements)
5
45
0
3
Order By: Relevance
“…Early correction of anesthesia-induced hypothermia in septic animal models improves outcomes (43). In humans, observational studies have shown that hypothermia independently predicts hospital mortality in the setting of sepsis (44), injury (45), and cardiac surgery (46). In the ICU, hypothermic patients with sepsis have higher levels of tumor necrosis factor-a and IL-6 (24) as well as a higher incidence of multiorgan dysfunction (47).…”
Section: Original Researchmentioning
confidence: 99%
“…Early correction of anesthesia-induced hypothermia in septic animal models improves outcomes (43). In humans, observational studies have shown that hypothermia independently predicts hospital mortality in the setting of sepsis (44), injury (45), and cardiac surgery (46). In the ICU, hypothermic patients with sepsis have higher levels of tumor necrosis factor-a and IL-6 (24) as well as a higher incidence of multiorgan dysfunction (47).…”
Section: Original Researchmentioning
confidence: 99%
“…Despite their frequency, there is a relative paucity of literature investigating the epidemiology and outcomes of patients with fever and hypothermia in general medicalsurgical populations. Studies to date have been limited by small numbers of patients (7,(11)(12)(13), have been conducted in single or specialized ICUs (11)(12)(13)(14), or have lacked detailed clinical information (2,15). Furthermore, few studies have evaluated both hypothermia and fever in a single study (13).…”
mentioning
confidence: 97%
“…44 In other studies evaluating nosocomial BSIs in elderly, S. aureus represented 7-24% and S. coagulase negative 14-25% of all these BSIs. 3,13,45 Most studies evaluating elderly with any BSI report S. aureus in 7-17% of BSIs 14,21,25,28,33,35,46-48 with variable rates of methicillin resistance.…”
Section: Microbiology Of Bsismentioning
confidence: 99%